2008
DOI: 10.1158/0008-5472.can-08-0215
|View full text |Cite
|
Sign up to set email alerts
|

An Anti–Transforming Growth Factor β Antibody Suppresses Metastasis via Cooperative Effects on Multiple Cell Compartments

Abstract: Overexpression of transforming growth factor B (TGF-B) is frequently associated with metastasis and poor prognosis, and TGF-B antagonism has been shown to prevent metastasis in preclinical models with surprisingly little toxicity. Here, we have used the transplantable 4T1 model of metastatic breast cancer to address underlying mechanisms. We showed that efficacy of the anti-TGF-B antibody 1D11 in suppressing metastasis was dependent on a synergistic combination of effects on both the tumor parenchyma and micro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
190
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(204 citation statements)
references
References 47 publications
12
190
0
1
Order By: Relevance
“…In our study, we used two strategies to block TGF-β signaling: (i) in a genetic model, TGF-β signaling was inhibited by stable transfection of tumor cells with a soluble TGF-β receptor (sTβRII), which functions as a "TGF-β trap," competing with TGF-β1 and -β3 for binding to TGF-β receptor ΙΙ; and (ii) in a pharmacologic model, TGF-β signaling was inhibited by a neutralizing antibody that blocks all three isoforms of TGF-β. The 4T1 tumors are known to express elevated levels of TGF-β and are sensitive to TGF-β blockade (4,8). We observed that both sTβRII transfection and 1D11 antibody administration significantly inhibited 4T1 tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In our study, we used two strategies to block TGF-β signaling: (i) in a genetic model, TGF-β signaling was inhibited by stable transfection of tumor cells with a soluble TGF-β receptor (sTβRII), which functions as a "TGF-β trap," competing with TGF-β1 and -β3 for binding to TGF-β receptor ΙΙ; and (ii) in a pharmacologic model, TGF-β signaling was inhibited by a neutralizing antibody that blocks all three isoforms of TGF-β. The 4T1 tumors are known to express elevated levels of TGF-β and are sensitive to TGF-β blockade (4,8). We observed that both sTβRII transfection and 1D11 antibody administration significantly inhibited 4T1 tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 69%
“…), impaired intratumoral drug delivery is an important physiological factor contributing toward chemoresistance (1,2). TGF-β is an important regulator of normal mammary gland development and function, as well as of the progression of mammary carcinomas (3)(4)(5)(6)(7)(8). Although the role of TGF-β in tumor progression and metastasis has been studied extensively, little is known about its impact on drug delivery.…”
mentioning
confidence: 99%
“…Additionally, other groups have shown that the spread of a transplantable model of metastatic breast cancer, 4T1 breast cancer cells, can be efficiently suppressed by administering an antibody that targets all three isoforms of the TGFb ligand. This work went on to show that TGFb neutralizing antibodies can have multiple cooperative effects on angiogenesis, immune cell function, and tumor cell viability, eventually leading to effective tumor control and reductions in metastasis [92]. These results illustrate the capacity to target the TGFb pathway in order to effectively inhibit metastatic events.…”
Section: Mouse Models Of Tgfβ and Metastasismentioning
confidence: 99%
“…TGF-␤'s disease promoting activities, together with animal studies that have demonstrated beneficial effects of inhibiting TGF-␤ in models of cancer and fibrosis (15)(16)(17)(18)(19)(20)(21)(22), have made them important targets for the development of inhibitors. However, despite clinical trials ongoing for nearly 2 decades using receptor kinase inhibitors, neutralizing antibodies, and other approaches, no TGF-␤ inhibitors have been approved for clinical use in humans (23,24).…”
mentioning
confidence: 99%